Environmental Impacts in the Alambique River Basin, Piemonte da Diamantina, Bahia - Almeida, Hortência Silva (2022)
Water is a diffuse, finite good, endowed with economic value that requires conservation management of the watershed as a planning unit. This article identified the environmental impacts of the watershed, describing the main aspects, the degrading factors and evaluated the associated environmental impacts, pointing out mitigating measures for the proper management of the Alambique River located in the municipality of Senhor do Bonfim/BA. To analyze the state of conservation of the water body, the Rapid Assessment Protocol (PAR) was used, and for the assessment of environmental impacts, the Listing Method was used to survey aspects (causes) and environmental impacts (consequences) and applied the Leopold's Matrix. On-site visits were carried out for systematic observation and application of the PAR. The findings point to the emergence of compliance with environmental standards for land use and occupation, with the competent public bodies responsible for monitoring and mitigating the negative impacts on the watershed.